ANALISIS ZONA POTENSI PENANGKAPAN IKAN BERDASARKAN SPL, KLOROFIL-A, DAN BOAT DETECTION SERTA MENGKAJI RZWP3K, LAMPUNG - Jodi Hans Sitorus; Aulia Try Atmojo; Samsul Bachri; Hardian Sy. Prayitno; Imam Komarita (Fakultas Perikanan dan Ilmu Kelautan, 2022)
In 2021, the Marine Affairs and Fisheries Office of Lampung Province only recorded fish volume and production data at the technical executive unit in Kota Agung. This will make a difficulty for fishermen outside the technical executive unit of Kota Agung to determine fishing locations and for researchers to determine the potential of all water areas. The study aimed to obtain the distribution value of Sea surface temperature (SST) and Chlorophyll-a, the results of potential fishing zones, and to analyze regulations related to fishing throughout Lampung waters. Determination of potential pelagic fish locations based on SST, Chlorophyll-a, and boat detection parameters. The data was obtained by utilizing AQUA-MODIS and SNPP-VIIRS Level 3 satellite imagery. The methods used are Inverse Distance Weighting (IDW) Interpolation and Kernel Density Estimation (KDE). In March-April 2022, areas of high potential for pelagic fish with SST 27-28°C and chlorophyll-a 1.1-1.9 mg/m³ are in the waters of Tanggamus Regency, South Lampung, East Lampung, and Bandar Lampung City. Whereas in the waters of West Lampung Regency, it has a low potential with SST 29-30°C and chlorophyll-a 2.2-3.1 mg/m³. The interviews with fishermen and the Marine Affairs and Fisheries Office of Lampung Province revealed that there were still violations of the application of RZWP3K in the Allowed Catches (JTB) by fishermen, with catches exceeding the allowed catches (5-10 tons per day). Therefore, the application of fishing permits (SIPI) for small fishermen 5-15 GT and fishing business permits (SIUP) need to be reaffirmed, especially in potential areas.